The Socialization of the Stages in implementing HOTS-Based in writing lesson plan For Educators - Wariyati Wariyati; Muhammad Noer Fadlan (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
Every educator who will implement a learning process should prepare every single thing needed. One of the most important need is a lesson plan which are used as guidelines for carrying out a learning process which include all integrated and matched plans that create to several other tools such as teaching materials, learning media, worksheets and assessments. These needs are able to accommodate the thinking process of students and they are having a thinking skill, especially high order thinking skills (HOTS). Every educator must have knowledge in preparing lesson plans that accommodate higher-order thinking skills. In order for educators to have this knowledge, socialization of the stages in preparing HOTS-based which implemented in lesson plan for educators is carried out.Keywords: Lesson Plan, HOTS, learning tools